2014
DOI: 10.1136/flgastro-2014-100489
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of long-term nasobiliary drainage to treat intractable pruritus in cholestatic liver disease

Abstract: IntroductionCholestasis related pruritus, secondary to intrahepatic and/or extrahepatic biliary obstruction is a common manifestation in chronic liver disease. Pruritus is difficult to treat, and results are often suboptimal. A stepwise medical approach is usually employed, followed by a trial molecular adsorbents recirculation system in medication resistant cases. Pruritus resulting in reduced quality of life is a variant syndrome eligible for liver transplantation in the setting of preserved synthetic functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…11 Similarly, Beuers et al reported that following a mean 4.1 days of NBD in three PBC patients, two were completely free of pruritus within 24 h. 12 following 7 days of NBD in six patients with intractable pruritus secondary to viral hepatitis A, B and E. 13 More recently, a UK single centre report of three patients (2 PBC, 1 BRIC) has suggested long-term NBD is successful in maintaining remission of pruritus. 14 In comparison to previous studies, our study is unique since it is a multicentre study and to the best of our knowledge, it is the largest retrospective study describing the utility of NBD in cholestatic pruritus. In addition to adding evidence to the reported advantages of NBD, our study attempts to answer some of the previously unanswered questions and uncertainties about NBD.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…11 Similarly, Beuers et al reported that following a mean 4.1 days of NBD in three PBC patients, two were completely free of pruritus within 24 h. 12 following 7 days of NBD in six patients with intractable pruritus secondary to viral hepatitis A, B and E. 13 More recently, a UK single centre report of three patients (2 PBC, 1 BRIC) has suggested long-term NBD is successful in maintaining remission of pruritus. 14 In comparison to previous studies, our study is unique since it is a multicentre study and to the best of our knowledge, it is the largest retrospective study describing the utility of NBD in cholestatic pruritus. In addition to adding evidence to the reported advantages of NBD, our study attempts to answer some of the previously unanswered questions and uncertainties about NBD.…”
Section: Discussionmentioning
confidence: 96%
“…reported complete remission of pruritus following 7 days of NBD in six patients with intractable pruritus secondary to viral hepatitis A, B and E . More recently, a UK single centre report of three patients (2 PBC, 1 BRIC) has suggested long‐term NBD is successful in maintaining remission of pruritus …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations